Malaysian Early Childcare and Childhood Education (ECCE) Curriculum: Perspectives of Malaysian ECCE Educationists - Hafsah, Taha; Zahyah, Hanafi (2020)
Upon realising the importance of early childhood education for the nation’s development, Malaysian government began to enhance the quality of the ECCE curriculum through policies and legislation. Such developments are evident in the government agenda and several initiatives, including the National Key Result Areas (NKRA) in the 11th Malaysia Plan, the Government Transformation Programme (GTP) and the Education Blueprint 2013-2025. The quality of the ECCE curriculum in Malaysia has not yet received the required attention, as the focus continues to remain largely on achieving quantitative academic targets. This qualitative study examined educationists’ perspectives on the quality of current Malaysian Early Childcare and Childhood Education (ECCE) curriculum. The study employed a semi-structured interview protocols to probe the views from 11 Malaysian educationists. It concludes that educationists believe the documented Malaysian ECCE curriculum today is already aligned with the holistic child development philosophy, but the country may need a higher impact programs of teacher education and training, to produce qualified and competent teachers who would implement the curriculum effectively.